Impact of a reduction in heating, cooling and electricity loads on the performance of a polygeneration district heating and cooling system based on waste gasification. (15th May 2018) - Kabalina, Natalia; Costa, Mário; Yang, Weihong; Martin, Andrew
Abstract: Polygeneration is a promising technology for enhancing the performance of traditional centralized district heating and cooling (DHC) systems since it enables the use of renewable energy sources and provides flexibility in supplying a range of value-added products. The main objective of this study is to evaluate how a reduction in heating, cooling and electricity loads would impact on the performance of a polygeneration DHC system based on waste gasification from thermodynamic, exergy, economic and environmental perspectives. To this end, system models considering hourly performance for a typical year of operation were established with either refuse derived fuel (RDF) or municipal solid waste (MSW) as feedstocks. The study reveals that with a decrease in heating, cooling and electricity loads the system, using RDF or MSW as the main fuel, is still capable of delivering energy services, but with reduced amounts of value-added products and less favourable overall system performance. For example, with RDF as the main fuel, when char, syngas, synthetic natural gas and hydrogen are produced with the gas turbine operating at 25% of its nominal value, with no heating and cooling supplies, the system thermodynamic efficiency is only 3.9%, as compared with 31.5% for the maximal heating, cooling and electricity supplies for the same group of value-added products. Nevertheless, under these conditions the system operation is still feasible and economically viable; specifically, annual revenues and discounted net cash flows are 6.4 and 11.1 mln USD, respectively. Highlights: Polygeneration district heating and cooling system based on waste gasification. Produces simultaneously electricity, heating, cooling and value-added products. Load impact on system thermodynamic, exergy, economic and environmental performance. Reduction of loads makes system operation still feasible and economically viable.